The Influence of Basic Accounting Course on Computerized Accounting Course with Self-Efficacy as a Moderating Variable - Zain Mide, Nuraisyah; Amin, Nursyamsi (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2024)
This research was conducted to examine the effect of basic accounting subject mastery on accounting computer subject mastery with self-efficacy as a moderating variable. The population in this study were students of the Accounting Department, Politeknik Negeri Ujung Pandang, Indonesia. The sample in this study amounted to 97 respondents. This research data is primary data obtained through the results of a questionnaire using Google Form and secondary data in the form of respondent's basic accounting values and the accounting computer value. The data analysis technique used is the Structural Equation Model with the SmartPLS®4 as the analysis tool. The results of the research show that (1) basic accounting subject mastery influences accounting computers subject mastery and (2) self-efficacy is unable to strengthen the influence of basic accounting on accounting computers. subject mastery. The novelty of this research is the use of self-efficacy as a moderating variable. The implications of this research are expected to provide information to institutions regarding the importance of basic accounting foundations for students because it will impact their ability to use accounting software which will be useful for their work readiness